(untitled) (Universal International Scientific Journal, 2026)
This scientific article analyzes the theoretical foundations of commercialization of research results, modern forms of innovative activity (startups, technology transfer, implementation of scientific developments into production), existing systemic problems, and specific proposals and solutions aimed at addressing them based on a comprehensive approach